Projeto de fundição de uma carcaça do sistema de direção para um veículo baja, assitido por simulação - Ferraz, Rafael Hehl Pinto (Universidade Federal de São Carlos, 2025)
This work aimed to develop a casting project for manufacturing the steering box housing of the Baja SAE UFSCar team vehicle. During the project, steps such as material selection, feeding and gating system design, and process variables definition were addressed. To ensure part quality and avoid defects like shrinkage porosity and cold shuts, the simulation software MAGMASOFT® 6.1 was used, allowing design optimizations before practical manufacturing. After the optimizations, the model was produced using 3D printing, and the mold was made with sand and phenolic resin (PEPSET). The casting was carried out using the A356 aluminum alloy. Despite some surface defects, the part showed good internal soundness. To validate the process, metallographic analyses were performed in different regions of the part, along with hardness tests, showing satisfactory results when compared with values found in the literature. This work also served as a foundation for future projects of the Baja UFSCar team, strengthening knowledge in the casting process and demonstrating the feasibility of this technology for manufacturing structural components of the vehicle.
Simulation-assisted casting design of a steering system housing for a baja vehicle
Keywords: Fundição; Baja SAE; Simulação; Magmasoft; Liga A356; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA DE TRANSFORMACAO